PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI MENGGUNAKAN ANIMAKER PADA MATERI STATISTIKA - Helmi Ilham Nabila; Nelly Fitriani; Wahyu Setiawan (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The aim of the investigation is to create practical and efficient mathematics learning media for classroom use using animaker-animated videos. The ADDIE model, comprising five stages, namely Analysis, Design, Development, Implementation, and Evaluation, was employed to carry out the Research and Development (R&D) method. The study was conducted at SMP Negeri 1 Margaasih, with ten ninth-grade students involved in a small-scale trial and 36 ninth-grade students in a large-scale trial. The validators were media experts, material experts, and math teachers. Microsoft Excel was utilized to assess the average response of students based on a feedback questionnaire. The outcomes revealed that the product was in line with the ADDIE research method, with a product feasibility of 84% for media experts, 65% for material experts, and 77% for teachers in the small-scale trial, and 96% for media experts, 87% for material experts, and 94% for teachers in the large-scale trial, indicating that it is highly feasible. The validated products were then tested on students through small and large-scale trials, with 87% showing very practical criteria. Therefore, animaker-animated video learning media on statistics material is both feasible and practical for use as a tool for learning mathematics.